2015
DOI: 10.17957/ijab/15.0045
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Rice Performance by Fermented Chitin Waste

Abstract: Fermented chitin waste (FCW), a by-product obtained from chitinase production using chitin fermentation, was evaluated for its properties for use as soil supplement based plant growth stimulator. Rice growth, yield and photosynthesis parameters were investigated following the growth of rice plants in organic fertilizer supplemented soil with the addition of 0.25, 0.50 or 1.00% (w/w) FCW in comparison with chemical fertilizer application. The application of FCW resulted in an increased photosynthetic pigment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These results suggest that residual effect of CHT powder increases the post-harvest soil pH. The results were supported by Kananont et al (2015) who conducted an experiment with Fermented chitin waste (FCW) along with CF = soil supplemented with chemical fertilizer and CMF = soil supplemented with chicken manure fertilizer. The results found that FCW @ 1% the ph differ significantly from 0.5% FCW, 0.25% FCW and the rest of the treatment.…”
Section: Ph Status Of the Post-harvest Soilmentioning
confidence: 68%
See 1 more Smart Citation
“…These results suggest that residual effect of CHT powder increases the post-harvest soil pH. The results were supported by Kananont et al (2015) who conducted an experiment with Fermented chitin waste (FCW) along with CF = soil supplemented with chemical fertilizer and CMF = soil supplemented with chicken manure fertilizer. The results found that FCW @ 1% the ph differ significantly from 0.5% FCW, 0.25% FCW and the rest of the treatment.…”
Section: Ph Status Of the Post-harvest Soilmentioning
confidence: 68%
“…From this study it can be suggested that residual effect of chitosan powder increase the organic carbon content in soil. The results were supported by Kananont et al (2015) who conducted an experiment and found that fermented chitin waste increase organic carbon content in soil and by Arif (2015) who found that chitosan application increases the level of organic carbon in soils.…”
Section: Organic Carbon Content In the Post-harvest Soilsmentioning
confidence: 70%
“…However, the impactful action of treatments T1 and T2 on the area of leaves and on the BSD severity in both conditions should be considered in a combined treatment of Tithonia diversifolia liquid extract and clam shells for more improvement of plantain vivoplants vigor. Indeed, the fermented chitin waste (FCW) have been recently shown to enhance the lettuce and rice performance by acting as a plant growth stimulator 30,31 . Further studies are needed to (1) understand the molecular mechanisms underlying the relationship between the improved vivoplants and the Tithonia diversifolia liquid extract, (2) evaluate this liquid extract effect on other bananas diseases and pests, as well as on other plants, (3) to position the improved vivoplants vis-à-vis the vitroplants known as the best banana seeds and (4) to access spatio-temporal and varietal variations of vivoplants responses.…”
Section: Discussionmentioning
confidence: 99%
“…ไคทิ นเป็ นพอลิ เมอร์ ที ่ ไม่ เป็ นพิ ษต่ อสิ ่ งแวดล้ อม ไม่ เป็ นอั นตรายต่ อทางเดิ นอาหารของสั ตว์ และไม่ ละลายในตั วท้ าละลายทั ่ วไป ส่ งผลให้ ไคทิ นมี ความล้ าบากในการน้ ามาใช้ ในกระบวนการทาง เคมี และบ่ งบอกลั กษณะต่ าง ๆ(Austin, 1984) อย่ างไรก็ ตาม จากงานวิ จั ยก่ อนหน้ านี ้ สามารถ อธิ บายลั กษณะสั ณฐานวิ ทยาของไคทิ นว่ าอยู ่ ในรู ปของของแข็ งและมี ทั ้ งโครงสร้ างที ่ เป็ นแอลฟาไคทิ น และบี ตาไคทิ น(Rudall and Kenchington, 1973) ไคทิ นสามารถน้ ามาใช้ ประโยชน์ ได้ หลากหลาย ทั ้ งลั กษณะเส้ นใย ฟิ ล์ ม ผง และฟองน้ ้ า(Yusof et al, 2003) การเตรี ยมสารอนุ พั นธ์ ของไคทิ นในรู ป ต่ าง ๆ ท้ าให้ ไคทิ นสามารถละลายในของเหลวได้ หากไคทิ นเกิ ดกระบวนการ deacetylation เกิ น 50% ท้ าให้ ไคทิ นละลายในตั วท้ าละลายได้ ซึ ่ งเป็ นลั กษณะพิ เศษของไคทิ นที ่ สามารถน้ าไปประยุ กต์ ใช้ ในด้ านต่ าง ๆ โดยขึ ้ นอยู ่ กั บชนิ ดของไคทิ นในสิ ่ งมี ชี วิ ตต่ าง ๆ(Aiba, 1991) นอกจากนี ้ ไคทิ นยั งเป็ น คาร์ โบไฮเดรตที ่ ย่ อยสลายได้ ตามธรรมชาติ อี กทั ้ งไคทิ นยั งน้ ามาใช้ ประโยชน์ ได้ หลากหลาย โดยท้ า หน้ าที ่ ต่ อต้ านแบคที เรี ย ยั บยั ้ งกิ จกรรมของรา(Rupley, 1964) ส่ งเสริ มการผลิ ตเอนไซม์ chitnase ของแบคที เรี ยในดิ น(Sashiwa et al, 1990) ยั บยั ้ งการบุ กรุ กของหนอนตั วกลมและเชื ้ อก่ อโรค รวมถึ งส่ งเสริ มความหลากหลายของจุ ลชี พในดิ น เพิ ่ มธาตุ อาหารพื ชในดิ น(Cretoiu et al, 2014) นอกจากนี ้ การน้ าไคทิ นไปผ่ านกระบวนการย่ อยสลายด้ วยเอนไซม์ ท้ าให้ เกิ ดสารอนุ พั นธ์ ที ่ เรี ยกว่ า ไค โทซาน ซึ ่ งสามารถละลายได้ ดี ในตั วท้ าละลายต่ าง ๆ และงานวิ จั ยก่ อนหน้ านี ้ พบว่ า ไคโทซาน(Aiba, 1991) ท้ าหน้ าที ่ ส่ งเสริ มผลผลิ ตของพื ช โดยเป็ นสารกระตุ ้ นการเติ บโต ชั กน้ าการป้ องกั นตนเองผ่ าน กิ จกรรมของเอนไซม์ กระตุ ้ นการท้ างานของของพื ชหลากหลายชนิ ด อย่ างไรก็ ตาม วั สดุ เหลื อทิ ้ งจาก อุ ตสาหกรรมการผลิ ตไคโทซานที ่ เรี ยกว่ า กากไคทิ น (chitin-rich residue) ยั งได้ น้ ามาใช้ ในการเพิ ่ ม ผลผลิ ตและการเติ บโตของพื ช ได้ แก่ ข้ าว(Kananont et al, 2016) ผั กสลั ดพั นธุ ์ บั ตเตอร์ เฮดและเรด โอ๊ ค(Muymas et al, 2015) งานวิ จั ยนี ้ เป็ นการศึ กษาผลของกากไคทิ นในฤดู ปลู กที ่ หนึ ่ งต่ อผลผลิ ตของผั กกาดหอมในฤดู ปลู กที ่ สอง โดยกากไคทิ นที ่ ใช้ ในการทดลองได้ มาจากการหมั ก Bacillus licheniformis strain SK-1 กั บไคทิ น(Kudan and Pichyangkura, 2009) Muymas et al (2015) ได้ น้ ากากไคทิ นที ่ ได้ จาก กระบวนการดั งกล่ าวมาใช้ เพิ ่ มผลผลิ ตผั กสลั ดพั นธุ ์ บั ตเตอร์ เฮดและเรดโอ๊ ค พบว่ า กากไคทิ นช่ วย ส่ งเสริ มให้ ผั กสลั ดทั ้ งสองพั นธุ ์ มี ผลผลิ ตมากขึ ้ นรวมถึ งท้ าให้ สมบั ติ ทางเคมี ของดิ นดี ขึ ้ น ซึ ่ งคาดว่ ากาก ไคทิ นท้ าหน้ าที ่ ทั ้ งเพิ ่ มธาตุ อาหารในดิ นและกระตุ ้ นการเจริ ญเติ บโตของพื ช และท้ าให้ ผั กสลั ดมี การดู ด ซึ มธาตุ อาหารได้ มากขึ ้ น ตลอดจนส่ งเสริ มให้ ผั กสลั ดมี ลั กษณะทางสรี รวิ ทยาบางประการเปลี ่ ยนแปลง ไป อย่ างไรก็ ตาม การใช้ กากไคทิ นในการเพิ ่ มผลผลิ ตของผั กสลั ดในแปลงปลู กของเกษตรกรที ่ ทดลอง ปลู ก 2 ฤดู ปลู กได้ มี การเติ มกากไคทิ นเพิ ่ มในวั สดุ ปลู กในแปลงก่ อนปลู กผั กสลั ดในฤดู ที ่ 2 ด้ วย ซึ ่ งกาก ไคทิ นที ่ เติ มในฤดู แรกอาจยั งหลงเหลื ออยู ่ ในดิ นและผลของกากไคทิ นในฤดู ปลู กที ่ หนึ ่ งต่ อการเติ บโต ของผั กสลั ดในฤดู ที ่ สองยั งไม่ มี การศึ กษา โดยงานวิ จั ยนี ้ ได้ มุ ่ งศึ กษาผลของกากไคทิ นที ่ คงเหลื อจากการ ปลู กฤดู ที ่ หนึ ่ งต่ อผลผลิ ตของผั กกาดหอมในฤดู ปลู กที ่ สอง จากการทดลองใช้ กากไคทิ นเพื ่ อเป็ นวั ...…”
unclassified